ABOMEY - Sjørslev, Inger (Tidsskriftet Antropologi, 2003)
The West African city Abomey was the centre of the kingdom Dahomey, notorious for its slave raids, ritual sacrifices of human beings, and its religious belief in vodhuns. Today a peaceful town in the state of Benin, its visual non-citylike impression provides the outset for reflections on what constitutes a city. The article digs into the history of the kingdom of Dahomey and relates how it was constructed on the basis of expansion and incorporation of its enemies through assimilation, but also symbolically expressed in rituals that celebrated the conquest of the enemies. Such stories are recounted today in the historical royal palace, the Musée Historique d’Abomey, where the famous bas-reliefs and the stories of how the kings’ palaces were built on the blood of the enemies testify to the historical drama of the kingdom. The article compares today’s city of Abomey with the neighbouring city of Bohicon, which at first glance seems to live up to expected standards of what constitutes a modern city much better than does Abomey. However, it is argued that commerce, exchange, heterogeneity and traffic are not enough to constitute a city. Historically, Abomey had an aura of holiness to it, which sprang from its placement at the centre of the kingdom, but also from its being the frame for the temples of the gods and the king. This gives rise to a question of what kind of holiness can be attributed to modern cities. If they are not “holy” by virtue of being cities of kings or historical centres, cities will have to create themselves for instance through performative culture and historical recreation.